2018
DOI: 10.2147/tcrm.s153397
|View full text |Cite
|
Sign up to set email alerts
|

Exercise habituation is effective for improvement of periodontal disease status: a prospective intervention study

Abstract: Background and purposePeriodontal disease is closely related to lifestyle-related diseases and obesity. It is widely known that moderate exercise habits lead to improvement in lifestyle-related diseases and obesity. However, little research has been undertaken into how exercise habits affect periodontal disease. The purpose of this study was to examine the effect of exercise habits on periodontal diseases and metabolic pathology.MethodsWe conducted a prospective intervention research for 12 weeks. The subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…We have previously contributed to studies comparing the effects of dietary restriction and exercise regimens in obese middle-aged men with NAFLD [ 18 , 19 , 20 , 21 ]. In a series of clinical and animal studies [ 22 ], we showed that exercise: (a) ameliorated hepatic fat accumulation and inflammation/fibrosis [ 18 ]; (b) increased the phagocytic capacity of Kupffer cells [ 19 ]; (c) increased the hepatic clearance of LPS and reduced the innate immune response to LPS [ 22 ]; (d) activated the antioxidative stress-responsive transcription factor nuclear factor erythroid 2–related factor 2 (Nrf2) and increased the anti-inflammatory and oxidative stress responses [ 18 ]; and, (e) ameliorated periodontitis and reduced the populations of certain periodontal bacterial taxa [ 21 ]. These results suggest that oral bacteria are important in the development and progression of NAFLD, and that an exercise regimen may change the composition of the oral microflora and ameliorate periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously contributed to studies comparing the effects of dietary restriction and exercise regimens in obese middle-aged men with NAFLD [ 18 , 19 , 20 , 21 ]. In a series of clinical and animal studies [ 22 ], we showed that exercise: (a) ameliorated hepatic fat accumulation and inflammation/fibrosis [ 18 ]; (b) increased the phagocytic capacity of Kupffer cells [ 19 ]; (c) increased the hepatic clearance of LPS and reduced the innate immune response to LPS [ 22 ]; (d) activated the antioxidative stress-responsive transcription factor nuclear factor erythroid 2–related factor 2 (Nrf2) and increased the anti-inflammatory and oxidative stress responses [ 18 ]; and, (e) ameliorated periodontitis and reduced the populations of certain periodontal bacterial taxa [ 21 ]. These results suggest that oral bacteria are important in the development and progression of NAFLD, and that an exercise regimen may change the composition of the oral microflora and ameliorate periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we aimed to analyze the residual saliva of previous study [ 21 ], conduct a metagenomic analysis of the oral microflora, and compare the metabolic activities of the microflora of obese patients with NAFLD and periodontal disease before and after a 12-week exercise regimen or a dietary regimen to define the changes in the oral environment and underlying any improvements.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, 40-70% of intensity resistance exercise program, which was applied 3 days a week for 8 weeks, was found to decrease AST and ALT levels in overweight individuals (Gholami, 2018). In a different study, it was found that exercise program applied for 12 weeks decreased AST values in obese individuals and did not change much in ALT (Omori et al, 2018). This study has shown that Resistance exercises have positive effects on blood lipids in general.…”
Section: Discussionmentioning
confidence: 51%
“…A total of seven studies reported their impact of dietary interventions in patients with periodontitis (Table ) (Fridell et al, ; Holmer et al, ; Jenzsch et al, ; Kondo et al, ; Omori et al, ; Woelber et al, ; Zare Javid et al, ). Their research protocols showed increased heterogeneity with study durations from 4 weeks to 12 months and sample sizes between 8 and 71 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent systematic review on the promotion of healthy lifestyles, smoking cessation was shown to be effective when applied in the dental practice while further evidence for dietary counselling in the dental setting was limited (Ramseier & Suvan, 2015 loss. Accordingly, with this systematic review, several studies were qualifying for more than one risk factor control intervention such as physical exercise (activity) and dietary changes (Omori et al, 2018) or weight loss, carbohydrate (dietary sugar) reduction and dietary…”
Section: Weight Loss In Periodontitis Patientsmentioning
confidence: 99%